Pilot Study on User Experience Analysis of Universitas Indonesia Library Website - Yulistiana Prasetya; Rahmi Rahmi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
User experience is an essential component in website development where information architecture needs to be considered. Information architecture can help make it easier for users to find what they are looking for and need on a website. In providing the information needed by users, Universitas Indonesia (UI) Library needs to analyse the relationship between user experience and user perceptions of information architecture. This research uses the Post-study System Usability Questionnaire (PSSUQ), Usability Metric for User Experience (UMUX), Standardized User Experience Percentile Rank Questionnaire (SUPR-Q), and Library Search UX instruments and received responses from 127 UI students. The results showed that library search, system capability, website navigation, trust, loyalty, and user interface significantly affect user perceptions of the information architecture of the Universitas Indonesia Library website. Additionally, information quality, interface quality, and system quality do not significantly affect user perceptions of the information architecture of the Universitas Indonesia Library website. This research is useful for further development of the UI Library website.